2013
DOI: 10.1021/ac402961t
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated Gas Chromatograph for Rapid, Trace-Level Determinations of Gas-Phase Explosive Marker Compounds

Abstract: A prototype microfabricated gas chromatograph (μGC) adapted specifically for the rapid determination of selected gas-phase marker compounds of the explosive 2,4,6-trinitrotoluene (TNT) at sub-parts-per-billion ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 32 publications
1
53
1
Order By: Relevance
“…As shown, the alkanes (compounds 3, 8, 11, and 13) eluted early from the 2 D μcolumn, as expected, and gave sharp peak clusters, with fwhm values ranging from 80 (C 7 ) to 280 ms (C 10 ). The alkene d-limonene and the set of four aromatics (compounds 1, 6,9,12,14) were all retained slightly longer than the alkanes and had fwhm values of 410− 480 ms, with little or no tailing evident. The diether 1,4-dioxane had slightly wider modulated peaks (fwhm = 532 ms).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…As shown, the alkanes (compounds 3, 8, 11, and 13) eluted early from the 2 D μcolumn, as expected, and gave sharp peak clusters, with fwhm values ranging from 80 (C 7 ) to 280 ms (C 10 ). The alkene d-limonene and the set of four aromatics (compounds 1, 6,9,12,14) were all retained slightly longer than the alkanes and had fwhm values of 410− 480 ms, with little or no tailing evident. The diether 1,4-dioxane had slightly wider modulated peaks (fwhm = 532 ms).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Table 1-1 Summary and comparison of µGC systemsprovides a detailed comparison of four µGC systems, including Zebra GC, and highlights the features, advantages and disadvantages of different system components. As seen, other reported µGC systems [19][20][21][22][23], while producing promising results, use individually fabricated chips which lead to extra care to avoid compound condensation in cold spots. Also, some of these systems still use conventional components to achieve high performance which can lead to increased energy consumptions or increased analysis time.…”
Section: Introductionmentioning
confidence: 99%
“…Less effort has been made toward the fabrication of other necessary μGC components, such as microvalves and micropumps, which are used extensively for fluidic routing and to provide gas flow. Usually, a μGC system is developed using commercially available valves and pumps [16][17][18] , and few research milestones have been accomplished toward microvalve miniaturization 14,19 . In one example, Terry et al 20 reported a magnetically actuated microvalve for sample injection in their seminal work on μGC development.…”
Section: Introductionmentioning
confidence: 99%